A new paradox of the digital economy - Structural sources of the limitation of GDP statistics. (November 2018) - Watanabe, Chihiro; Tou, Yuji; Neittaanmäki, Pekka
Abstract: The Internet has dramatically changed the way we conduct business and our daily lives by provided us with unprecedented services and conveniences. However, contrary to such accomplishments, productivity in industrialized countries is now experiences an apparent decline. This has raised the question of a possible productivity paradox in the digital economy. The limitation of GDP statistics in measuring the advancement of the digital economy has thus become an important subject. This paper analyzed the structural sources of this problem. Utilizing the results of empirical analyses of national, industrial, and individual behavior in the digital economy, solutions to these critical issues were investigated. Based on the two-faced nature of information and communication technology (ICT) and the fact that people's preferences extend beyond economic value, the concept of uncaptured GDP was postulated and spinoff dynamism to a new co-evolution among advancement of the Internet, increasing dependence on uncaptured GDP, and a shift in people's preferences was reviewed. This provided new insight and suggested a transformative direction to address the limitation of using GDP statistics in the digital economy. Highlights: A new paradox of the digital economy was discussed. Structural sources of the productivity decline in the digital economy was identified. Limitations of GDP in measuring the advancement of the digital economy was identified. New insights for measuring the digital economy were explored. Significant role of soft innovation resources was postulated.